Characterisation of collagen type I/ type II composite scaffolds for osteochondral tissue engineering - Tamaddon, M (2014)
The field of tissue engineering has potential to provide a superior alternative to current surgical treatments. Biologically inspired scaffolds have recently gained considerable attention in this field. The goal of this thesis was to develop and characterise the layers of an osteochondral scaffold following the composition and structure of cartilage, the cartilage-bone interface and underlying bone to treat osteoarthritis or defects in bone and cartilage. Monomeric collagens were used as the basis of these scaffolds, as they can mitigate the issue of antigenicity and may improve the reliability of the scaffolds due to the lack of native crosslinks. Monomeric collagen type I alone and mixed with different amounts of hydroxyapatite formed the layers corresponding to calcified cartilage and subchondral bone. Collagen fibrils were made by in vitro fibrillogenesis. The preparations were characterised in terms of their molecular interaction; hydroxyapatite was attached electrostatically and covalently to collagen. The addition of hydroxyapatite and the formation of fibrils increased the rigidity of the collagen chains and subsequently increased the viscosity of the preparations. This affected the pore size of the final scaffolds; the pores were more dependent on growth than nucleation of ice crystals and more greatly influenced by suspension viscosity. The increase in rigidity of collagen chains with hydroxyapatite or fibrillogenesis led to an increase in the compressive modulus of the scaffolds up to 10 times. The modulus of the solid material and pore anisotropy were the main factors affecting the compressive modulus. The scaffolds were biocompatible and able to induce bone marrow stem cells to produce matrix-molecule collagen type I without any differentiation or growth factors. Monomeric collagen type II alone and mixed with equal amounts of chondroitin sulphate formed the layers corresponding to different zones of cartilage. Fibrillogenesis was performed in vitro. Chondroitin sulphates attached to collagen mainly by electrostatic forces, which were weakened when the collagen was made fibrillar. This interaction caused the loss of chondroitin sulphate in the cell culture media and thus a negative or no contribution to cell proliferation, but significantly increased chondrogenic differentiation. The addition of chondroitin sulphate and fibrillogenesis increased the rigidity of the collagen chains and the viscosity of suspensions, thereby affecting the pore structure of the final scaffolds. A very important finding was that stem cells produced mostly collagen type II matrix molecules on these scaffolds, which differed from the production of collagen type I on type I scaffolds. The hypothesis that the chemical differences in composition lead to different microstructure, mechanical properties and cell behaviour is confirmed. The developed scaffolds were greatly promising for osteochondral regeneration. The scaffolds were invaded, resorbed and remodelled by stem cells, and they were able to direct chondrogenesis and osteogenesis by tailoring the scaffold properties. This has great implications for clinical use. The main shortcomings were 1) their low compressive modulus, 2) their extreme contraction in cell culture media and 3) loss of chondroitin sulphate.